The Guidelines for Balanced Diet and Healthy Lifestyles during Pregnancy: The Management of Health and Morbidity in Pregnancy - Jensen, Megan E. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Pregnancy is a critical time in determining maternal health and future offspring health. Diet and lifestyle practices in the preconception and gestational period play an important role in optimising the health of both mother and child and in determining the risk of certain morbidities during pregnancy, including diabetes and hypertension, as well as their management. This Special Issue will collate the most recent research on the guidelines for dietary intake (including individual nutrients, dietary patterns, diet quality and food restrictions/avoidance) and lifestyle recommendations (including sleep, physical activity and environmental exposures) during pregnancy and the role they play in determining maternal and fetal health outcomes during pregnancy. Original research, systematic reviews and meta-analyses are preferred; however, narrative reviews are also welcome. Manuscripts that investigate nutrition/lifestyle factors as exposures during pregnancy and their impact on health during pregnancy are preferred; however, articles which examine the guidelines for, and/or the role of, diet and healthy lifestyles in the preconception period will also be considered, where the outcome is measured during pregnancy. Articles which examine maternal/offspring outcomes in the neonatal period may also be considered where the diet/lifestyle exposure was measured during gestation.